2023
DOI: 10.3390/jcm12062423
|View full text |Cite
|
Sign up to set email alerts
|

A Cone Beam CT Study on the Correlation between Crestal Bone Loss and Periapical Disease

Abstract: The aim of this study was to determine whether the degree of bone loss around teeth can be linked to the loss of vitality of adjacent teeth and periapical disease, which necessitates root canal treatments. Three hundred and twenty-one full maxilla cone-beam computed tomography scans were examined. The parameters investigated included the degree of crestal bone loss in relation to the cementoenamel junction, the presence/absence of apical periodontitis, and the presence/absence of root canal treatments. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Bergmans et al showed that the dentin disc with a thickness of 1 mm was inoculated with actinomyces and streptococcus in the same proportion, and after three times of irradiation with 1.5w Nd: YAG laser, it was found that the morphology of bacteria gradually changed with the increase of irradiation times, and finally the bacteria were completely destroyed 22 . The pulp tissue and periodontal tissue are anatomically communicating with each other, and there are mixed infections dominated by anaerobic bacteria in both the periodontal pocket and the infected pulp 23 . The inflammation and immune response caused by them are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergmans et al showed that the dentin disc with a thickness of 1 mm was inoculated with actinomyces and streptococcus in the same proportion, and after three times of irradiation with 1.5w Nd: YAG laser, it was found that the morphology of bacteria gradually changed with the increase of irradiation times, and finally the bacteria were completely destroyed 22 . The pulp tissue and periodontal tissue are anatomically communicating with each other, and there are mixed infections dominated by anaerobic bacteria in both the periodontal pocket and the infected pulp 23 . The inflammation and immune response caused by them are similar.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The pulp tissue and periodontal tissue are anatomically communicating with each other, and there are mixed infections dominated by anaerobic bacteria in both the periodontal pocket and the infected pulp. 23 The inflammation and immune response caused by them are similar. In this study, after laser‐assisted root canal cleaning, the periodontal index of patients, including PLI, BI, GI, and the levels of inflammatory indicators IL‐6, TNF‐α, and CRP, were all lower than those of the 1% NaClO group, which further indicating that the periodontal recovery and inflammation inhibition of patients after laser‐assisted root canal therapy were better than those in 1% NaClO alone.…”
Section: Discussionmentioning
confidence: 99%